RANCANG BANGUN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS WEB PADA SMK ISLAMIC CENTRE CIREBON - Siti Sahronih; Lulu Syarifatul Munawaroh (PERISKOP : Jurnal Sains dan Ilmu Pendidikan, 2020)
This research is motivated by the low creative thinking ability of students which is influenced by several factors including the learning carried out by the teacher is less stimulating towards increasing creative thinking skills, namely the lack of use of appropriate learning media. Students do not get assignments that can hone their thinking skills and generate creative ideas or something new. Based on these problems, one of the efforts to improve students' creative thinking skills in this study is to apply learning media that can hone students' thinking skills, namely crossword puzzle learning media. This research uses Classroom Action Research (CAR), which consists of four stages, namely planning, implementation, observation and reflection. This research was carried out at SD Negeri Karanglayung with a sample of 16 fifth grade students. This research was carried out in two cycles, where from cycle to cycle there was a significant increase, namely the acquisition of the percentage value of teacher skills in the first cycle of 77%, in the second cycle of 93 %. The value of the percentage of student activity in the first cycle was 79%, in the second cycle it was 95%. The percentage value of students' creative thinking skills in the first cycle was 69%, in the second cycle it was 84%. Thus it can be seen that the use of crossword puzzle learning media that researchers apply in the learning process can improve students' creative thinking skills